Flies without Borders : Lessons from Chennai on Improving India's Municipal Public Health Services - Gupta, Monica Das; Dasgupta, Rajib; Kugananthan, P.; Rao, Vijayendra; Somanathan, T.V.; Tewari, K.N. (Taylor and Francis, 2020)
India’s cities face key challenges to improving public health outcomes. First, unequally distributed public resources create insanitary conditions, especially in slums – threatening everyone’s health, as suggested by poor child growth even among the wealthiest. Second, devolving services to elected bodies works poorly for highly technical services like public health. Third, services are highly fragmented. This paper examines the differences in the organisation and management of municipal services in Chennai and Delhi, two cities with sharply contrasting health indicators. Chennai mitigates these challenges by retaining professional management of service delivery and actively serving vulnerable populations − while services in Delhi are quite constrained. Management and institutional issues have received inadequate attention in the public health literature on developing countries, and the policy lessons from Chennai have wide relevance.